Effect of regioisomers of hydroxystearic acids as peroxisomal proliferator‐activated receptor agonists to boost the anti‐ageing potential of retinoids. (5th September 2021) - Rawlings, Anthony V.; Wandeler, Eliane; Bendik, Igor; Fuchs, Pascale; Monneuse, Jean‐Marc; Imfeld, Dominik; Schütz, Rolf
Abstract: Introduction: We report on the in vitro and ex vivo effects of chiral ( R )‐10‐hydroxystearic acid (10‐HSA) compared with other mono‐hydroxystearic acid regioisomers and stearic acid (SA) together with its benefit when combined with retinol. Methods: Following treatment with hydroxystearic acids peroxisomal proliferator‐activated receptor alpha (PPARα) activity was determined in a luciferase reporter gene assay, collagen type I was assessed in primary human dermal fibroblasts by immunohistochemistry, modification of the intracellular fibroblast collagen proteome was studied by mass‐spectrometry‐based proteomics and collagen type III was assessed by immunohistochemistry on human ex vivo skin. Results: 10‐HSA was the most effective PPARα agonist (15.7× induction; p < 0.001), followed by 9‐HSA (10.1× induction) and then 12‐HSA (4.9× induction) with 17‐HSA (1.7× induction) being similar to the effects of stearic acid (1.8× induction). Collagen type I levels were increased in primary human fibroblasts by 2.12× and 1.56× for 10‐HSA and 9‐HSA, respectively, in vitro with the10‐HSA being significant ( p < 0.05), whereas 12‐HSA and SA had no statistical effect over the untreated control. 10‐HSA and 12‐HSA modified the intracellular fibroblast collagen proteome slightly with significant increases in collagen alpha‐1 (VI) and alpha‐3 (VI) proteins but only 10‐HSA increased levels of collagen alpha‐2 (V), alpha‐1 (III), alpha‐1 (I) and alpha‐2 (I) (all p < 0.05) with the increases being significantly different between 10‐HSA and 12‐HSA for collagen alpha‐1 (I), collagen‐3 (VI) and collagen alpha‐2 (I) ( p < 0.01). Collagen type III in ex vivo skin was increased +47% ( p < 0.05) by 0.05% (1.7 mM) retinol, +70% ( p < 0.01) by 0.01% (0.33 mM) 10‐HSA and the combination increased levels by +240% ( p < 0.01 for either ingredient). Conclusion: Chiral ( R )‐10‐HSA has been shown to be superior to 9, 12 and 17‐HSA as a PPARα agonist. Moreover, 10‐HSA stimulated collagen synthesis in monolayer fibroblast culture as assessed by proteomics and immunohistochemically. Furthermore, we also show the synergistic effects of 10‐HSA with retinol on collagen III synthesis in skin explants. These results further highlight the efficacy of 10‐HSA as a cosmetically acceptable PPARα agonist and anti‐ageing ingredient. Abstract : Chiral ( R )‐10‐HSA has been shown to be superior to 9‐HSA, 12‐HSA and 17‐HSA as a PPARα agonist. Moreover, 10‐HSA stimulated collagen synthesis in monolayer fibroblast culture as assessed by proteomics and immunohistochemically. Furthermore, we also show the synergistic effects of 10‐HSA with retinol on collagen III synthesis in skin explants highlighting the efficacy of 10‐HSA as a cosmetically acceptable PPARα agonist and anti‐ageing ingredient. Abstrait: Introduction: Nous rapportons les effets in vitro et ex vivo de l'acide chiral (R)‐10‐hydroxystéarique (10‐HSA) par rapport à d'autres régioisomères d'acide mono‐hydroxystéarique et à l'acide stéarique (SA) ainsi que ses avantages lorsqu'il est associé au rétinol. Méthodes: Après un traitement avec des acides hydroxystéariques, l'activité du récepteur alpha activé par les proliférateurs peroxysomaux (PPARα) a été déterminée dans un test du gène rapporteur de la luciférase, le collagène de type I a été évalué dans les fibroblastes dermiques humains primaires par immunohistochimie, la modification du protéome du collagène des fibroblastes intracellulaires a été étudiée par spectrométrie de masse. La protéomique et le collagène de type III ont été évalués par immunohistochimie sur la peau humaine ex vivo. Résultats: la 10‐HSA était l'agoniste PPARα le plus efficace (induction 15, 7X ; p<0, 001), suivi de la 9‐HSA (induction 10, 1X) puis de la 12‐HSA (induction 4, 9X) avec la 17‐HSA (induction 1, 7X) étant similaire aux effets de l'acide stéarique (induction 1, 8X). Les niveaux de collagène de type I ont été augmentés dans les fibroblastes humains primaires de 2, 12X et 1, 56X pour la 10‐HSA et la 9‐HSA respectivement in vitro, la 10‐HSA étant significative (p<0, 05) : alors que la 12‐HSA et la SA n'ont eu aucun effet statistique sur le témoin non traité. La 10‐HSA et la 12‐HSA ont légèrement modifié le protéome du collagène des fibroblastes intracellulaires avec des augmentations significatives des protéines de collagène alpha‐1 (VI) et alpha‐3 (VI), mais seule la 10‐HSA a augmenté les niveaux de collagène alpha‐2 (V), alpha ‐1 (III), alpha‐1 (I) et alpha‐2 (I) (tous p<0, 05) avec des augmentations significativement différentes entre 10‐HSA et 12‐HSA pour le collagène alpha‐1 (I), le collagène‐ 3 (VI) et Collagène alpha‐2 (I) (p<0, 01). Le collagène de type III dans la peau ex vivo a augmenté de +47 % (p<0, 05) de 0, 05 % (1, 7 mM) de rétinol, de +70 % (p<0, 01) de 0, 01 % (0, 33 mM) de 10‐HSA et la combinaison a augmenté les niveaux de +240 % (p<0, 01 pour chaque ingrédient). Conclusion: La chiral (R)‐10‐HSA s'est avérée supérieure à 9, 12 et 17‐HSA en tant qu'agoniste de PPARα. De plus, la 10‐HSA a stimulé la synthèse de collagène dans la culture de fibroblastes monocouche telle qu'évaluée par protéomique et immunohistochimique. De plus, nous montrons également les effets synergiques de la 10‐HSA avec le rétinol sur la synthèse du collagène III dans les explants de peau. Ces résultats soulignent en outre l'efficacité de la 10‐HSA en tant qu'agoniste de PPARα et ingrédient anti‐âge cosmétiquement acceptable.